2003
DOI: 10.1007/s00268-003-6645-0
|View full text |Cite
|
Sign up to set email alerts
|

Perforated Peptic Ulcer: Main Factors of Morbidity and Mortality

Abstract: Abstract. It is well stated in the literature that medical treatment for peptic ulcer is based on a combination of proton pump inhibitors (PPIs) and antibiotics to eradicate Helicobacter pylori. This treatment is associated with a high rate of immediate success and a low rate of recurrence at 12 months, although it is not effective in all patients. Peptic ulcer (PU) perforation is a serious problem that leads to high complication and mortality rates. Surgical treatment, with its various possibilities, constitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
85
1
12

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(120 citation statements)
references
References 14 publications
20
85
1
12
Order By: Relevance
“…For ulcer perforation, standard treatment is immediate intervention with either simple closure or a more complex surgical procedure (8,9). Delayed treatment is probably a major prognostic fac- Unstratified estimates and values stratified for the presence of heart and renal disease.…”
Section: Peptic Ulcer Perforationmentioning
confidence: 99%
See 1 more Smart Citation
“…For ulcer perforation, standard treatment is immediate intervention with either simple closure or a more complex surgical procedure (8,9). Delayed treatment is probably a major prognostic fac- Unstratified estimates and values stratified for the presence of heart and renal disease.…”
Section: Peptic Ulcer Perforationmentioning
confidence: 99%
“…Peptic ulcer bleeding and perforation are common medical emergencies, with an in-hospital or 30-day mortality of ϳ10% for bleeding ulcers (7,8) and up to 25-40% for ulcer perforation (9). Patients with diabetes may have poorer outcomes after peptic ulcer complications due to diabetic angiopathy (6), delayed ulcer healing (10), blurring of symptoms due to autonomic neuropathy, and increased risk of bacterial sepsis (11).…”
mentioning
confidence: 99%
“…On the other hand, numerous studies have shown that the presence of accompanying diseases has a significant effect on postoperative mortality and morbidity. In these studies, pulmonary diseases, hypertension (HT), diabetes mellitus (DM), and cardiac diseases were found to be of importance with varying frequency (5,27,28). In our study, the presence of DM, HT, renal failure, heart failure, COPD, and malignancies was observed to be related with a significantly increased risk of postoperative mortality and morbidity.…”
Section: Discussionmentioning
confidence: 55%
“…[1] Peptic ulcer disease is the most common cause of duodenal perforation. [1,2] Peptic ulcer disease is a frequent pathology that is caused by different disorders. Helicobacter pylori infection, nonsteroidal anti-inflammatory drugs, liver cirrhosis, hyperparathyroidism, and chronic pancreatitis are related to peptic ulcer disease.…”
Section: Resultsmentioning
confidence: 99%
“…[2,7,23] The technical difficulties of suturing in laparoscopic and endoscopic approaches have led to research studies about sutureless repair for duodenal perforations. [7,23,24] Application of effective sutureless repairing techniques for intestinal perforations is being studied with new chemical agents to create a proper minimally invasive technique.…”
Section: Discussionmentioning
confidence: 99%